Hydroplane : Fictions - Steinberg, Susan, 1966- (Book collections on Project MUSE., 2006)
Hydroplane is a story collection filled with the urgency of erotic obsession. Its breathless voices, palpable in their desire, are propelled by monomania, rushing from one preoccupation into another: a garage, a painting class, a basketball game, boys. Their words take on kinetic force, an almost headlong momentum, as though, while reading, one were picking up speed, veering out of control. The past returns. Rumination are continuous. A stranger at a bus stop is indistinguishable from the narrator's deceased grandfather; party guests turn ghoulish, festivities merge with nightmares.